Anti-Tumor Effects of BDH1 in Acute Myeloid Leukemia - Han, Fei; Zhao, Huanhuan; Lu, Jun; Yun, Weina; Yang, Lingling; Lou, Yude; Su, Dan; Chen, Xin; Zhang, Shixuan; Jin, Hanwei; Li, Xiang; Sun, Jie; et al. (Frontiers in Oncology, 2021)
Dysregulation of ketone metabolism has been reported in various types of cancer. In order to find out its role in acute myeloid leukemia (AML) pathogenesis, we first analyzed the expression levels of 10 key genes involved in ketone metabolism in AML blasts and CD34+ hematopoietic stem cells (HSCs) from healthy donors. We found that the expression level of BDH1 was significantly lower in AML than in normal HSCs. The downregulation of BDH1 gene expression in AML cell lines as compared with normal HSCs was further confirmed with real-time RT-PCR. Analysis of TCGA and other database revealed that the downregulation of BDH1 was associated with worse prognosis in AML patients. In addition, we showed that overexpression of BDH1 inhibited the viability and proliferation of AML cells. In contrast, BDH1 knock-down promoted AML cell growth. Collectively, our results suggest the previously unappreciated anti-tumor role of BDH1 in AML, and low BDH1 expression predicts poor survival.